They accuse: architecture and urban criticism… written by novelists - Muñoz, Mauricio (Universidad Antonio Nariño, 2021)
By comparing two quite opposite descriptions of the same city by different writers, the article begins proposing a reflection about which is the type of narration truly necessary when studying the relationship between the city and literature. Hence, from the purpose of fiction writing in general, until the need from writers to exercise criticism in the style of the famous I accuse published by Émile Zola, the author points out the differences among those more idyllic texts written by the persons involved in the productin of the city, with those more drastic ones conceived by novelists. Finally, the author concludes that the novel is a place for reflection where the writer reveals his/her critical positions; therefore, he/she deliberately avoids focusing on the qualities of urban experiences to concentrate on the typical conflicts of the city.